Reversible phase transformation phenomenon in titanium dioxide films: evidence beyond interface-nucleation and dissolution-precipitation kinetics - Gautam, Subodh K.; Singh, Jitendra; Shukla, D. K.; Pippel, E.; Poddar, P.; Singh, Fouran (Acta Materialia, 2018)
The re-crystallization kinetics and rutile to anatase reversible phase transformation (PT) in nano crystalline titanium dioxide (TiO2) are reported. Initially, an amorphous TiO2 film is used for the present study and in situ isothermal annealing dependent nucleation and growth kinetics of anatase and rutile phase is studied at low temperature (similar to 523 K) and well explained using Johnson Mehl AvramiKolmogorov (JMAK) model. The anatase nanocrystallite (NCs) transformation into rutile phase is reported with isothermal annealing for longer time and temperature dependent annealing in lower temperature range 523 K-673 K and explained using interface-nucleation mechanism. Furthermore, the thermodynamic stability of rutile NCs and lattice stress-induced reversible PT in nano-sized rutile TiO2 are confirmed in moderate temperature range (623 K- 973 K) and well explained using x-ray diffraction, micro-Raman spectroscopy and near edge x-ray absorption fine structure spectroscopy studies. However, annealing at higher temperature (1123 K- 1323 K) induces the growth of anatase NCs and their natural transform into rutile phase are explained by well-known dissolution precipitation mechanism. Activation energy of rutile PT is quantified and found higher for dissolution-precipitation mechanism than that for interface nucleation at earlier stage. Thus, overall PT kinetics at different temperature range is well understood by invoking in three step mechanism: 1) early stage anatase-to-rutile transformation is dominated by interface-nucleation, II) then intermediate stage reversible rutile-to-anatase PT and, Ill) at later stages, anatase-to-rutile PT is controlled by dissolution precipitation mechanism. (C) 2018 Acta Materialia Inc. Published by Elsevier Ltd. All rights reserved.
Keywords: Dissolution-precipitation kinetics; Interface-nucleation mechanism; Johnson-Mehl-Avrami-Kolmogorov (JMAK) approach; Reversible phase transformation

Micro-Raman investigations on zirconium oxide film during swift heavy ion irradiation to study crystalline-to-crystalline phase transformation kinetics by cascade overlap model - Singh, Fouran; Rawat, Mukesh; Gautam, Subodh K.; Ojha, Sunil (Journal of Applied Physics, 2019)
In situ micro-Raman studies are reported to monitor the evolution of the tetragonal phase in a monoclinic zirconium oxide thin film under swift heavy ion irradiation with increasing ion fluences. Structural changes in the irradiated film are observed as compared to the virgin sample, evident from an evolution of the tetragonal phase beyond critical ion fluence. The interpretation of experimental data allows for an in-depth understanding of irradiation induced stiffening of phonon and crystalline-to-crystalline phase transformation in ZrO2 thin films. Irradiation induced peak broadening and uniform shifting of fundamental Raman modes are observed mainly in the anion (i. e., oxygen atom) dominant frequency region and give a direct indication of the accumulation of structural disorder in the oxygen sublattice of the ZrO2 film. A qualitative approach is followed to understand the kinetics of such a crystalline-to-crystalline phase transformation. Experimental results reveal that the cascade overlap model with the requirement of about six multiple ion impacts provides an excellent fit to data, and the same is further confirmed by x-ray diffraction data. Thus, this study suggests that such in situ studies envisage a better and more authentic insight into the kinetics of phase transformations under similar nonequilibrium conditions.